Analysis Of Student Satisfaction In View Of Academic Atmosphere And Quality Of Educators - Fathan, Ahmad (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2022)
One of the main tasks of educational institutions is to educate students, and one way is to provide satisfaction. Satisfaction/pleasure of students can be a trigger for enthusiasm for learning and have an impact on increasing academic/non-academic achievement. Things that are directly related to this are lecturers and academic activities. Therefore, having quality lecturers and building a healthy academic environment is a necessity. This condition is the reason for this study to examine student satisfaction in learning which is influenced by the academic atmosphere and the quality of the teachers. This study uses quantitative principles, where the research data is in the form of numbers obtained through distributing questionnaires, and is analyzed using mathematical/statistical calculations, namely linear regression. The research sample was Pamulang university students as many as 380 people, with an incidental technique. The results of the study show that feelings of satisfaction/pleasure can increase student learning activeness both inside and outside the classroom, so that it is possible to increase academic/non-academic achievements. The interesting thing from this finding is that qualified lecturers and a good academic environment have a large level of contribution to students' feelings of satisfaction/enjoyment in learning. In fact, a feeling of pride was awakened, which gave birth to an attitude of love/caring for the campus and its lecturers.